Laser photocoagulation for radiation retinopathy after ophthalmic plaque radiation therapy. Issue 6 (27th May 2005) - Finger, P T; Kurli, M
Abstract : Aim: To evaluate the use of scatter laser photocoagulation to prevent radiation related retinopathy, maculopathy, and loss of vision. Methods: This was an interventional case series. 66 eyes with posterior choroidal melanomas treated by ophthalmic plaque radiation therapy were reported. Of these patients, 50 were selected because they developed radiation retinopathy; 45 of these were treated with sector scatter laser photocoagulation to regress clinically evident radiation retinopathy. 16 additional patients (considered to be "high risk" to develop radiation retinopathy) were also treated. Results: Radiation retinopathy was noted to appear at a mean interval of 26 months following plaque treatment. Laser photocoagulation regressed radiation retinopathy in 29 (64.4%) of the 45 patients treated after the onset of radiation retinopathy (17 with only retinopathy, 10 with a combination of retinopathy and maculopathy, and two with only maculopathy). Of the 16 patients who received laser treatment before clinical evidence of retinopathy, one developed radiation maculopathy and two retinopathy without maculopathy (all three responded to additional laser photocoagulation). In the 45 patient group, vision loss of more than three lines was attributable to radiation maculopathy in seven (15.5%). None of the patients in the prophylactic laser group lost more than three lines of vision as a result of maculopathy. Conclusion: Sector scatter argon laser photocoagulation induced regression of radiation retinopathy. Though early treatment of radiation retinopathy appears to be more effective, a more long term and prospective randomised study will be needed to prove efficacy.